Psychological characteristics child-parent relationships in foster care - Svidenska, G. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article presents the problem of socialization of orphaned children in foster home. Empirically proved that the affection is a basis of child- parent relationship in a foster home. The effective social support can provide the overcome of traumatic experience for child and will acquire a positive experience of living in a family.